"Ascertaining the Truth about the Religion and Ways of the Deifiers of ʿAlī": The Qajar Elite and the Ahl-e Ḥaqq. Issue 1 (January 2022) - Kurin, Gennady
Abstract : This paper presents some of the preliminary findings of the research on the history and religion of the Ahl-e Ḥaqq in nineteenth century Iran. It seeks to shed light on the Qajar-era statesmen's efforts to learn more about and thus better understand the otherwise enigmatic community, their origins, identities, beliefs, and practices as well as political loyalties. In particular, the article discusses arguably the most important text pertaining to the group and produced in late nineteenth century Iran, addresses the question of its authorship and sources, seeks to contextualize its composition and finally offers its full translation. Lastly, the paper offers a partial review of the most important Persian-language research and scholarship on the subject, points to several hitherto untapped primary sources for the study of the Ahl-e Ḥaqq, and also discusses the major actors and trends essential to understanding of and further research on the history of the community during the period in question and beyond.